ARL Physics Web Pages: An Evaluation by Established, Transitional and Emerging Benchmarks - Jane C. Duffy (Issues in Science and Technology Librarianship)
This study provides an overview of the range of characteristics among Association of Research Libraries Physics web pages. Current academic web literature was examined and organized into three streams: design-oriented literature, function-oriented literature and goal-oriented literature. From these streams, a series of six benchmarks by which ARL physics pages could be measured, were developed. From the first category, design-oriented literature, the following benchmarks were developed: 1) Ease of navigation; 2) Logic of presentation; and 3) Representation of all forms of information. From the second category, function-oriented literature, the following benchmarks were developed: 4) Engagement of the discipline; 5) Interactivity of page. From the third category, goal or mission-oriented literature, the last benchmark was developed: 6) Identification of audience. It was hypothesized a) that adoption of the benchmarks derived from the design stream would be "established", b) that those derived from the functional stream would be in a "transitional" phase, i.e., moving toward an established adoption and c) that the benchmark derived from literature concerned with goal and mission issues would be in the "emerging" stage of adoption. Results indicate the validity of these assumed adoption patterns.